Barley Genes as Tools to Confer Abiotic Stress Tolerance in Crops - Gürel, Filiz; Öztürk, Zahide N.; Uçarlı, Cüneyt; Rosellini, Daniele (Frontiers in Plant Science, 2016)
Barley is one of the oldest cultivated crops in the world with a high adaptive capacity. The natural tolerance of barley to stress has led to increasing interest in identification of stress responsive genes through small/large-scale omics studies, comparative genomics, and overexpression of some of these genes by genetic transformation. Two major categories of proteins involved in stress tolerance are transcription factors (TFs) responsible from the re-programming of the metabolism in stress environment, and genes encoding Late Embryogenesis Abundant (LEA) proteins, antioxidant enzymes, osmolytes and transporters. Constitutive overexpression of several barley TFs, such as C-repeat binding factors (HvCBF4), dehydration-responsive element-binding factors (HvDREB1) and WRKYs (HvWRKY38), in transgenic plants resulted in higher tolerance to drought and salinity, possibly by effectively altering the expression levels of stress tolerance genes due to their higher DNA binding affinity. Na+/H+ antiporters, channel proteins, and lipid transporters can also be the strong candidates for engineering plants for tolerance to salinity and low temperatures.